PABPN1: molecular function and muscle disease. (24th May 2013) - Banerjee, Ayan; Apponi, Luciano H.; Pavlath, Grace K.; Corbett, Anita H.
<x xml:space="preserve">Abstract</x> The polyadenosine RNA binding protein polyadenylate‐binding nuclear protein 1 (PABPN1) plays key roles in post‐transcriptional processing of RNA. Although PABPN1 is ubiquitously expressed and presumably contributes to control of gene expression in all tissues, mutation of the PABPN1 gene causes the disease oculopharyngeal muscular dystrophy (OPMD), in which a limited set of skeletal muscles are affected. A major goal in the field of OPMD research is to understand why mutation of a ubiquitously expressed gene leads to a muscle‐specific disease. PABPN1 plays a well‐documented role in controlling the poly(A) tail length of RNA transcripts but new functions are emerging through studies that exploit a variety of unbiased screens as well as model organisms. This review addresses (a) the molecular function of PABPN1 incorporating recent findings that reveal novel cellular functions for PABPN1 and (b) the approaches that are being used to understand the molecular defects that stem from expression of mutant PABPN1. The long‐term goal in this field of research is to understand the key molecular functions of PABPN1 in muscle as well as the mechanisms that underlie the pathological consequences of mutant PABPN1. Armed with this information, researchers can seek to develop therapeutic approaches to enhance the quality of life for patients afflicted with OPMD.